2002
DOI: 10.1038/oby.2002.20
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Inhibits Leptin Production by Cultured Rat Adipocytes

Abstract: Leptin is a key mediator in the neuroendocrine regulation of energy homeostasis and appetite. An in vivo study that raised leptin concentrations at high altitudes associated with loss of appetite (1) led us to speculate that low oxygen (hypoxia) might be the key stimulus for leptin secretion from adipocytes. Because leptin has angiogenic effects as well as vascular endothelial growth factor (2) and leptin secretion from non-adipocytes, human trophoblastic cells (3) are increased in culture under hypoxic condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 6 publications
1
14
1
Order By: Relevance
“…Yasumasu et al (2002) have reported about 50% decreased leptin secretion in case of in vitro cultured adipocytes exposed to low oxygen concentration. There are two studies on human subjects in which decrease in leptin levels are reported at HA (Vats et al 2004, Zaccaria et al 2004).…”
Section: Discussionmentioning
confidence: 96%
“…Yasumasu et al (2002) have reported about 50% decreased leptin secretion in case of in vitro cultured adipocytes exposed to low oxygen concentration. There are two studies on human subjects in which decrease in leptin levels are reported at HA (Vats et al 2004, Zaccaria et al 2004).…”
Section: Discussionmentioning
confidence: 96%
“…A higher leptin per body weight content was observed in our hypoxic group at 8 weeks, suggesting that, most probably, the origin of the high leptin is not only from the adipocytes. Although clinically leptin serves as a useful marker of adiposity, reflecting the total lipid content in humans [33], Yasumasu et al [34] showed that hypoxia does not stimulate leptin secretion from adipocytes; leptin secretion during this condition comes from non-adipocytes.…”
Section: Discussionmentioning
confidence: 98%
“…Leptin was previously shown to stimulate lipolysis and oppose the antilipolytic action of adenosine (48). Furthermore, sustained hypoxia and IH increased plasma leptin levels and gene expression (6,49), even though contradictory findings have also been reported (50,51). However, it seems unlikely that leptin is the causal mechanism linking IH exposure with increased lipolysis and whole-body metabolic impairments; this is because plasma leptin levels, as well as leptin and leptin receptor gene expression, in adipose tissue remained unaffected in our study, whereas lipolysis was strongly augmented.…”
Section: Discussionmentioning
confidence: 79%
“…Sensitivity of the lipolytic pathway to isoprenaline stimulation, assessed as half-maximal effective concentration (EC 50[iso] ), was unaffected by either IH exposure or acipimox treatment (EC 50[iso] = 1.1 6 0.4, 0.6 6 0.4, 1.3 6 0.5, and 1.5 6 0.5 nmol/L for control, IHexposed, acipimox-treated control, and acipimox-treated IH-exposed groups, respectively; two-way ANOVA, P . 0.05).…”
Section: The Effect Of Acipimox On Adipocyte Lipolysis and Plasma Ffamentioning
confidence: 99%
See 1 more Smart Citation